2019
DOI: 10.5607/en.2019.28.5.628
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 and Downstream Intracellular Signaling Proteins Play Critical Roles in the Cell Proliferation of Neuroblastoma, Meningioma and Pituitary Adenoma

Abstract: Leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) has been reported to play critical roles in the proliferation of various cancer cells. However, the roles of LGR5 in brain tumors and the specific intracellular signaling proteins directly associated with it remain unknown. Expression of LGR5 was first measured in normal brain tissue, meningioma, and pituitary adenoma of humans. To identify the downstream signaling pathways of LGR5, siRNA-mediated knockdown of LGR5 was performed in SH-SY5Y neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…LGR5 stimulates NB stem cell proliferation and self‐renewal by potentiating the Wnt/β‐catenin signaling (Xu et al, 2019). LGR5 inhibits Wnt/β‐catenin signaling by binding to its ligand R‐spondin which is Wnt signaling agonist and promotes NB oncogenesis (Hwang et al, 2019). The binding of Wnt ligands to LRP5 activates downstream Dsh protein that causes the breakdown of cytoplasmic degradation complex (Gsk3‐β, APC, and Axin) that earlier phosphorylated cytoplasmic β‐catenin and restricts its translocation to the nucleus (Rosenbluh et al, 2014).…”
Section: Wnt Signaling In Nbmentioning
confidence: 99%
“…LGR5 stimulates NB stem cell proliferation and self‐renewal by potentiating the Wnt/β‐catenin signaling (Xu et al, 2019). LGR5 inhibits Wnt/β‐catenin signaling by binding to its ligand R‐spondin which is Wnt signaling agonist and promotes NB oncogenesis (Hwang et al, 2019). The binding of Wnt ligands to LRP5 activates downstream Dsh protein that causes the breakdown of cytoplasmic degradation complex (Gsk3‐β, APC, and Axin) that earlier phosphorylated cytoplasmic β‐catenin and restricts its translocation to the nucleus (Rosenbluh et al, 2014).…”
Section: Wnt Signaling In Nbmentioning
confidence: 99%
“…12 Meanwhile, estrogen receptor positive de novo meningiomas significantly involve chromosomes 14 and 22. 13 The study by Hwang et al 14 reported that the expression levels of heterogeneous nuclear ribonucleoprotein (hnRNP) family proteins were significantly higher in pituitary adenomas and meningiomas than that in normal brain tissues. Leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) and its downstream signaling pathways play an pivotal role in pituitary tumor, meningioma, and other brain tumors.…”
Section: Pituitary Adenoma Associated With Meningiomamentioning
confidence: 99%
“…In a study by Lorena et al[8],protein expression patterns of distant metastases in NB xenograft mouse model were identi ed by Quantitative proteomics. Hwang et al [9] found a total of 12 proteins differentially regulated after LGR5 knockdown, including Wnt/β-catenin signaling and hnRNP family, indicating that LGR5 and its downstream signaling may play a critical role in NB by hyperactivation of alternative pre-mRNA processing.…”
Section: Introductionmentioning
confidence: 99%